GAME WHAC-A-MOLE BERBASIS AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN HEWAN KARNIVORA DAN HERBIVORA - Fajar Hariadi (Jurnal Akrab Juara, 2019)
Visual media are very useful to transfer information from one person to others. The game is an interactive visual media where players can interact with what they saw on the digital screen. It can be used to make a pleasing interactive education. Combining the popular game whack-a-mole with Augmented Reality can make children easily understand which animal is Carnivore and which one is a herbivore. So we hope this prototype can support traditional education to transfer the information to children.